PENGARUH EFIKASI DIRI, KEBUTUHAN AKAN PRESTASI DAN KEBERANIAN MENGAMBIL RISIKO TERHADAP NIAT BERWIRAUSAHA MAHASISWA - Al Habib, Muhammad Farid; Rahyuda, I Ketut (E-Jurnal Manajemen; Vol 4 No 9 (2015), 2015)
Various problems are faced by Indonesia such as unemployment, poverty, high population and the enactment of ASEAN economic community. Role of the entrepreneurs is needed in order to overcome these problems by creating jobs. Students are expected to become educated entrepreneurs who are capable to build the businesses. The purpose of this study was to determine the direct effect of self-efficacy and need for achievement toward students’ entrepreneural intention, as well as the indirect effect through the courage to take risks in influencing the entrepreneurial intention of FEB Unud students who do not take course in entrepreneurship. This study used a sample of 120 students with proportionate stratified random sampling method by using path analysis. Results showed that self-efficacy and need for achievement have positive and significant impact direcltly on entrepreneurial intention. Intervening variables of risk-taking have positive and significant impact on entrepreneurial intention. Furthermore,indirect effect of self-efficacy and need for achievement has positive impact and significant as the indirect coefficient value is bigger than the coefficient direct value.
Keywords: self-efficacy, need for achievement, risk-taking, entrepreneural intention, path analysis.